THE MORAL TEACHINGS OF PROPHET MUHAMMAD (PBUH) EMBEDDED IN THE MAULID SIMTUD DURAR AUTHORED BY SAYYID ALI AL-HABSHI - Arif Maulana; Abdul Majid; Nasokah (Alphateach (Jurnal Profesi Kependidikan dan Keguruan), 2025)
This research is motivated by issues observed in the author's environment such as moral crises and violencestemming from a lack of understanding regarding the moral values ​​embedded in the Simtud Durar maulid text. The study aims to: 1) understand the concept of Prophet Muhammad’s (PBUH) moral character education; 2) examine the content and discussion of the Simtud Durar text; and 3) identify the moral teachings of Prophet Muhammad (PBUH) implicit in Simtud Durar. This is a library-based study that gathers primary data from the Simtud Durar text and secondary data from various supporting sources relevant to the research topic. Content analysis is employed to analyze the data. The study yields several conclusions regarding the moral teachings of Prophet Muhammad (PBUH) found in Simtud Durar: first, moral conduct toward Allah SWT, demonstrated by praising Him, seeking His pleasure, and expressing gratitude; second, conduct toward the Messenger of Allah, practiced by frequently reciting shalawat (blessings upon the Prophet); third, conduct toward oneself, characterized by modesty, gentleness, generosity, and dignity; fourth, conduct toward family, marked by a compassionate attitude; and fifth, conduct toward society, characterized by a strong sense of social responsibility and truthfulness. Regarding its content, the study concludes that Simtud Durar comprises 14 chapters that collectively recount the birth and passing of Prophet Muhammad (PBUH) while conveying values ​​of moral character education. Furthermore, the moral values ​​of Prophet Muhammad (PBUH) found in Simtud Durar can be applied in daily life by strengthening faith in Allah SWT, practicing honesty, maintaining modesty, and fostering compassion and mutual respect among fellow human beings.